PENGEMBANGAN LKPD SIFAT KOLIGATIF LARUTAN BERBASIS PBL UNTUK MENGUKUR KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Jaman Fahmi; Budiman Anwar; Wulan Dwi Safitri; Dwi Sapri Ramadhan; Dian Wardana; Dimas Ridho; Ekin Dwi Arif Kurniawan; Ahmad Fauzi Syahputra Yani (Universitas Samudra, 2026)
This study aims to develop a PBL (Problem-Based Learning) based Student Worksheet (LKPD) on the topic of colligative properties of solutions that are valid, reliable, and feasible to be used as an instrument for assessing students’ critical thinking skills. This research employed a Type 1 Design and Development Research (DDR) model consisting of the stages of Analysis, Design, Development, Try-out, and Evaluation, although its implementation was limited to the Try-out stage. The study involved validators comprising university lecturers and chemistry teachers, as well as 106 twelfth-grade science students from MAN 2 Model Medan selected through purposive sampling. Data were collected using semi-structured interview guidelines and assessment questionnaires and subsequently analyzed using the Content Validity Ratio (CVR), Content Validity Index (CVI), item validity tests, reliability analysis, item difficulty index, discrimination index, normality, and homogeneity tests. The findings indicate that out of 16 initial items, 11 essay items were found to be valid (Pearson Corelation > 0,3) and reliable with internal reliability coefficients categorized as good (Cronbach’s Alpha > 0.7). The difficulty indices of the items ranged from difficult to easy, with discrimination indices categorized as moderate to very good. Therefore, the developed PBL-based LKPD is deemed feasible for use in measuring students’ critical thinking skills in the context of colligative properties of solutions.